Use of retroauricular tubular flap for ear helix and ear lobe reconstruction - Renato da Silva Freitas; Caio Munaretto Giacomazzo; Silvia Helena Mandu; Maria Cecilia Closs Ono; Alfredo Duarte da Benjamin Silva (Revista Brasileira de Cirurgia Plástica)
Ear defects are frequent and result of many etiologies, even though ear reconstruction remains a challenge in plastic reconstructive surgery due to anatomy and local tissue paucity. Despite being rarely used, the tubular retroauricular flap presents as an alternative for helix and lobule reconstruction. In this article, the authors describe the operative technique and report a case in which it was used. Also, plastic surgeons and laypeople rated the operative results of four cases of ear reconstructions using the tubular retroauricular flap. The final esthetic result was rated as good or excellent by 35% of laypeople and 50% of plastic surgeons, whereas the operative result was rated as good or excellent by 70% of laypeople and 80% of plastic surgeons. Thereby the findings and authors’ experience, we can recommend the tubular retroauricular flap technique for reconstructing ear helix border defects.